APPLICATION RADIOACTIVE METHODS IN THE SYSTEM OF HYDRO-GEOLOGICAL MONITORING OF TERRITORIES OF THE TECHNOGENIC LOADING - VYZHVA, S.; DEINEKO, S.; ASTASHKINA, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Experience of application of radioaktive researches for definition hydro-geological soils parameters is considered. Possibility application degree of saturation, which received by the gamma-gamma density logging and neutron-neutron overthermal logging data, for depth definition ground waters level is proved.